Lattice Boltzmann Model for a Class of Viscous Wave Equation (Advances in Applied Mathematics and Mechanics, 2024)
In this work, a new lattice Boltzmann model for a class of viscous waveequation is proposed through the variable transformation, which eliminates the mixedthird order partial derivative term of time and space. Some numerical tests are performed to validate the present model, and the results show that the present model hasa second-order convergence rate in space.